Ethics in culture : the dissemination of values through literature and other media - Erll, Astrid; Grabes, Herbert; Nünning, Ansgar (Spectrum Literaturwissenschaft ;, 2008)
Alongside the recent cultural turn in the humanities, there has been a noticeable return to ethical considerations. With regard to literature as well as other media, this has rekindled awareness of a tension, antagonism, or even disparity between ethics and aesthetics. This volume of articles takes a more systematic and cross-disciplinary approach to the widely mooted ethical turn in literature and other media than has been pursued so far. It brings together a wide range of critical perspectives from literary studies, media and cultural memory studies, and philosophy, tracing the complex and s.